Reprodutibilidade e construção na escultura Modernista - Gonçalves, Patrícia, 1994- (2018)
This dissertation intends to study two sculptural procedures that contributed to the transition from Classicism to Modernity – Reproducibility and Construction. Therefore, a case study of the Portuguese and international artistic context is presented and analysed, from the end of the nineteenth century until the middle of the twentieth, which was designated by Modernism. Reproducibility was not a product of the twentieth century, but of a long process that led to the paradigm shift at the beginning of this century. Its impact on Artistic Teaching is observed, based on the analysis of three learning models, which opted for reproduction as the main pedagogical methodology. Reproduction of works of art, whether by teaching or by the artists' initiative, contributed to the proliferation of the sculptures themselves and, consequently, emphasized the didactic and plastic nature of reproducibility. The interest in the practice of technical reproduction, as a mean of artistic creation, began in the late nineteenth century, with Auguste Rodin, pioneer of modern sculpture. Also Pablo Picasso and Marcel Duchamp were precursors and influential during the Modernism, and the importance for their artistic productions in this investigation, is due to the fact that both of them took advantage of the reproduction of their own works, through the creation of series and editions. In the case of Constantin Brancusi, the use of reproduction was related to the way the Romanian sculptor took up the same themes throughout his artistic career. There were also sculptors that recovered themes and works of other artists, and Alberto Giacometti and Umberto Boccioni are examples of that. The construction is addressed according to a perspective that is the Picasso’s papiers collés, later called collage, the origin of the construction process. In this sense, it is argued that the collage lead to two different ways to build: one more focused on the potential of materials and meaning of objects owned by sculptors who were in charge of selecting, retrieving and re-contextualised within the art world, as was the case the assemblages, of appropriations, the ready-mades and objects Dada and Surrealist; the other, more directed to the actual construction technique, with "new" industrial materials and innovative technical processes. In short, it must be kept in mind that construction is the technical procedure that best characterizes modern sculpture, which has reached its apogee with Minimalism